Rozwiąż równanie.
a) 3(2x-1)-5(x-3)+6(3x-4)=83
b) 0,2x+0,5x+5(5x-1)-2,7x=6,5
c) 0,3(0,4x-1,2)+0,36x-0,6
a)
6x - 3 - 5x + 15 + 18x - 24 = 83
19x = 95
x = 5
b)
0,2x+0,5x+25x-5-2,7x=6,5
23x=11,5
x=0,5
c)
0,12-0,36+0,36x-0,6
???????
a. 6x-3-5x-15+18x-24=83
6x-5x+18x=83+3+15+24
29x=125/29
x=4,3
b. 0,7x+25x-5-2,7x=6,5
0,7x+25x-2,7x=6,5+5
23x=11,5/23
x=0.5
c. 0,12x-36+0,36x-0,6
0,12x+0,36x=36+0,6
0,48x=36,6/0,48
x= 76,25
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
a)
6x - 3 - 5x + 15 + 18x - 24 = 83
19x = 95
x = 5
b)
0,2x+0,5x+25x-5-2,7x=6,5
23x=11,5
x=0,5
c)
0,12-0,36+0,36x-0,6
???????
a. 6x-3-5x-15+18x-24=83
6x-5x+18x=83+3+15+24
29x=125/29
x=4,3
b. 0,7x+25x-5-2,7x=6,5
0,7x+25x-2,7x=6,5+5
23x=11,5/23
x=0.5
c. 0,12x-36+0,36x-0,6
0,12x+0,36x=36+0,6
0,48x=36,6/0,48
x= 76,25